Severe Prinzmetal’s Angina Inducing Ventricular Fibrillation Cardiac Arrest - Bashar Khiatah; David Philips; Jonathan Dukes; Amanda Frugoli (Case Reports in Cardiology)
Prinzmetal’s angina is a vascular spasm of the coronary artery that can mimic acute coronary syndrome. It is rarely responsible for ventricular arrhythmias and cardiac arrest; however, survivors with these complications are at increased risk for recurrent ventricular arrhythmias and sudden cardiac death. This is true despite the presence of normal cardiac function and optimal medical therapy. Thus, this select population should be considered for an implantable cardioverter defibrillator (ICD). In this case vignette, we describe a healthy 48-year-old female with ventricular fibrillation arrest, followed by recurrent ventricular tachyarrhythmias caused by Prinzmetal’s angina.